2019
DOI: 10.1177/0363546519854450
|View full text |Cite
|
Sign up to set email alerts
|

An Anterior Cruciate Ligament Failure Mechanism

Abstract: Background: Nearly three-quarters of anterior cruciate ligament (ACL) injuries occur as “noncontact” failures from routine athletic maneuvers. Recent in vitro studies revealed that repetitive strenuous submaximal knee loading known to especially strain the ACL can lead to its fatigue failure, often at the ACL femoral enthesis. Hypothesis: ACL failure can be caused by accumulated tissue fatigue damage: specifically, chemical and structural evidence of this fatigue process will be found at the femoral enthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 29 publications
6
64
0
Order By: Relevance
“…It has taken us more than 10 years to acquire data demonstrating that in fact ACL fatigue failure is a possibility along with direct evidence of the microdamage involved. In Chen et al, 2 we demonstrated that one can cause damage to accumulate at the molecular, cellular, and ultrastructural levels at the ACL femoral enthesis of cadavers under repetitive submaximal loading, and we also observed a similar damage signature in the femoral entheses of ACLs removed from living athletes at the time of their surgical repair. Savio Woo showed that the maximal tensile load that a healthy young adult ACL could withstand under 1 loading cycle is about 500 lbf.…”
supporting
confidence: 79%
“…It has taken us more than 10 years to acquire data demonstrating that in fact ACL fatigue failure is a possibility along with direct evidence of the microdamage involved. In Chen et al, 2 we demonstrated that one can cause damage to accumulate at the molecular, cellular, and ultrastructural levels at the ACL femoral enthesis of cadavers under repetitive submaximal loading, and we also observed a similar damage signature in the femoral entheses of ACLs removed from living athletes at the time of their surgical repair. Savio Woo showed that the maximal tensile load that a healthy young adult ACL could withstand under 1 loading cycle is about 500 lbf.…”
supporting
confidence: 79%
“…Repetitive loading has also been shown to cause fatigue failure of the ACL, with in vitro and in vivo studies of human joints identifying the femoral enthesis as a site commonly susceptible to disruption. 15 While repetitive loads were not applied to the joint in the current study, the femoral insertion was still identified as a site of histopathological remodeling that coincided with the temporal decline in ACL strength. This biological remodeling likely occurs in response to excessive loading at the time of injury, given that the femoral enthesis is a common site of failure in mouse models of intentional ACL rupture (ie, loading beyond subcritical thresholds).…”
Section: Discussionmentioning
confidence: 77%
“…Some research has pointed that fatigue could cause acute ACL lesion [12][13][14][15][16][17][18][19][20][21][22][23] , but the de nition of ACL fatigue lesion has not been revealed completely from academic eld. Until 2013, Ashton-Miller 's biomechanical study based on knee model through donated human corpses has demonstrated that repetitive pressure-applying jump is likely to cause ACL fatigue damage, but Miller 's research is only limited in biomechanical eld, not involved with clinical research [24][25] . For two of the cases, arthroscopy surgery was performed and concluded that ACL fatigue lesion without trauma history manifested as ligament relaxation and partial femoral end damage.…”
Section: Discussionmentioning
confidence: 99%